Prototyping the Power Hall: a decision-making process - Christina Buckingham (Science Museum Group Journal)
Interactive gallery interpretation is seen as a valuable tool for engaging families with the subject of science and engineering. It can offer many opportunities for creating active learning experiences and can help stimulate visitor interest and motivation (Falk et al, 2004). However, with such an abundance of technologies and techniques to choose from, it can be challenging for exhibition teams to decipher which interactive interpretation approach will deliver the most impactful results for their future visitors. The practice research outlined in this study identified that there was currently no defined method to compare the success of one proposed interactive interpretation approach to another from the perspective of both family and science engagement, despite these two elements being essential components in the design thinking process.